Reclaiming the Narrative: A Critical Discourse Analysis of Donald Trump's 2024 Super Tuesday Campaign Speech - Tito Dimas Atmawijaya (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
This study critically analyzes Donald Trump's 2024 campaign speech using Fairclough's Critical Discourse Analysis (CDA) framework to explore how his rhetorical strategies construct power relations and reinforce ideological divisions. By examining key rhetorical devices such as pronouns, metaphors, hyperbole, and Repetition, the study reveals how Trump's language fosters a collective identity among his supporters, positioning them as defenders of